Implementation of Marketing Strategies in Educational Institutions - M. Asep Fathur Rozi; Bustanul Arifin (Tarbiyah Departement collaboration with AMCA, 2020)
Marketing education services is a social and managerial process to get what is needed and to chill through creating offers, exchanging valuable products with other parties in the field of education. The purpose of this study is to determine the implementation of marketing strategies in educational institutions. The research method used is a descriptive qualitative approach to the study of literature from books, journals and other sources. The results show that to create a synergistic relationship between educational institutions, the education service user is not only used as a customer, but is also positioned as a manager, and also as a partner. Education service users are involved in policy making and planning in education. Thus the user of educational services also determines the development of educational institutions that ultimately affect the development of children.